Al-Qushayri's efforts in reconciling Sharia and reality (Haqiqa) - Mahpol, Shahrizal; Sayyid Omar, Sayyid Hadratul-Lutf; Yusuf, Muhammad Saif al-Anwar; al-Hakim, Muhammad Luqman (Universiti Teknologi MARA, Kelantan, 2018)
The goal of this study stems from the need to identify the efforts of one of the most prominent Sufi figures who played a vital and effective role in reconciling Sharia and Reality (Haqiqa). Therefore, this study addressed the introduction of al-Qushayri (d. 465 AH), his efforts, and the extent of the role he played in clarifying the close connection between the practical side and the spiritual side in some of his writings. The study relied on a descriptive qualitative approach using content analysis to collect information from primary sources and literature related to the subject of the study. The study reached several results, most importantly: that al-Qushayri was a Sunni Sufi scholar whose reputation was widespread among scholars as "The Reconciler between Sharia and Reality." He had a special methodology in authorship characterized by the symbolic/allusive (ishari) trend, which suggests that apparent meanings in various sciences have subtle meanings hidden from some people's minds. This is an innovative methodology from which subsequent scholars benefited in their writings, such as al-Ghazali, Ibn Ajiba, and others. In conclusion, this study presents a Sufi personality considered a measure by which the integrity of a particular Sufi and the extent of his commitment to the foundations of Sharia are tested.